AB0796 Disease Modifying Anti Rheumatic Drugs Improve Cardiovascular Autonomic Neuropathy in Psoriatic Arthritis. (9th June 2015) - Syngle, A.; Verma, I.; Krishan, P.
Abstract : Background: Cardiovascular autonomic neuropathy (CAN) is the commonest risk predictor for sudden cardiac death in autoimmune rheumatic diseases. 1-2 As yet, there is no therapeutic treatment of cardiovascular autonomic neuropathy in psoriatic arthritis (PsA). Even, the impact of most commonly employed disease modifying antirheumatic drugs (DMARDs) therapy on cardiovascular autonomic neuropathy in PsA is not known. Objectives: To investigate the efficacy of DMARDs on cardiovascular autonomic neuropathy in PsA. Methods: In this perspective open label study, twenty DMARD naive PsA patients who fulfilling the CASPAR (Classification Criteria for Psoriatic Arthritis) criteria and 20 age and sex matched healthy controls were recruited. Cardiovascular autonomic neuropathy was diagnosed by applying the five cardiovascular reflex tests according to Ewing. Disease activity was assessed by 28-joint-count disease activity score (DAS28) and disease activity score in psoriatic arthritis (DAPSA). ESR was measured by Westergreen method and CRP level was determined using standard commercial kits. Autonomic measures were double blinded to the physician and patients for the study duration. Therefore, the patients were treated without influence of the autonomic function data. All clinical investigations were performed at baseline and after weeks 12. Results: Cardiovascular reflex tests were impaired significantly among the PsA patients compared with well matched healthy subjects (p<0.05). Parasympathetic dysfunction was more prominent than sympathetic dysfunction. After 12 weeks treatment, parasympathetic dysfunction (HR response to deep breath and standing) significantly (p<0.05) improved in patients with PsA, while there was no significant improvement in sympathetic function. 55% (11/20) DMARD naive patients had severe autonomic neuropathy score. After treatment, 72.7% (8/11) improvement was seen in severe autonomic neuropathy in DMARD naive PsA patients. Patients with normal cardiovascular autonomic function had no change in their cardiovascular autonomic function after 12 weeks treatment with synthetic DMARDs. Conclusions: These study results suggest parasympathetic autonomic dysfunction is more prominent than sympathetic dysfunction in PsA. Synthetic DMARDs improved parasympathetic dysfunction in PsA. References: Milovanovic B et al. Srp Arh Celok Lek. 2010; 138:26-32. Syngle et al. Clin Rheumatol. 2013;32:59-64. Acknowledgements: We are very grateful to University Grant Commission, New Delhi (Govt. of India) for providing the research fellowship [No. F.10-15/2007 (SA-I)]. Disclosure of Interest: None declared